CLEAs of Candida antarctica lipase B (CALB) with a bovine serum albumin (BSA) cofeeder core. Study of their catalytic activity - Guauque Torres, María del Pilar; Foresti, María Laura; Ferreira, Maria Lujan (Biochemical Engineering Journal)
Highly active CALB cross-linked enzyme aggregates (CLEAs) were synthesized using a layered methodology based on the synthesis of a cross-linked protein cofeeder core over which an external layer of lipase was later cross-linked. The layered CALB CLEAs were characterized in terms of their catalytic activity in three different test reactions: esterification of oleic acid and ethanol in absence of solvents, esterification of oleic acid and heptanol in organic medium, and hydrolysis of triolein in emulsioned medium. The impact of the cross-linker/protein mass ratio on CLEAs activity, and its evolution with storage time were evaluated in the solventless synthesis of ethyloleate. The amount of cross-linker used showed to be a key parameter for the evolution of the catalytic activity of CLEAs during storage. Under the best conditions found, hyperactivated CALB CLEAs with up to 188% of recovered activity in ethyl oleate synthesis were obtained. In terms of hydrolytic activity mature layered CALB CLEAs showed a retained activity of 68%. The assay of dried mature layered CALB CLEAs in heptyl oleate synthesis showed catalytic activities much higher than the one exhibited by free CALB, reaching 1 h-fatty acid conversions of 14% and 2%, respectively. The high catalytic activity shown by layered CALB CLEAs, suggests that they are an interesting alternative specially for the catalysis of fatty acid esterifications in both organic and solventless medium. Fil: Guauque Torres, María del Pilar. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Bahía Blanca. Planta Piloto de Ingeniería Química (i); Argentina Fil: Foresti, María Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Bahía Blanca. Planta Piloto de Ingeniería Química (i); Argentina. Consejo Nacional de Investigaciones Cientificas y Tecnicas. Oficina de Coordinacion Administrativa Houssay. Instituto de Tecnologia En Polimeros y Nanotecnologia; Argentina Fil: Ferreira, Maria Lujan. ...